Comparison of paired human nasal and bronchial airway epithelial cell responses to rhinovirus infection and IL‐13 treatment. Issue 1 (2nd May 2018) - Roberts, Nicole; Al Mubarak, Reem; Francisco, David; Kraft, Monica; Chu, Hong Wei
Abstract: Background: Because of its advantage as a minimally invasive procedure, nasal brushings have been increasingly used and proposed as a valuable approach to study lower airway diseases in lieu of bronchial epithelial cells. However, there is limited or conflicting evidence pertaining to whether nasal samples can be surrogates to bronchial samples. The goal of the present study is to test whether nasal epithelial cells have similar antiviral and inflammatory responses to IL‐13 treatment and rhinovirus infection, a condition mimicking virally induced asthma exacerbation. Nasal and bronchial airway epithelial cells taken from the same patient were cultured under submerged and air–liquid interface (ALI) culture in the absence or presence of rhinovirus and IL‐13 treatment. Inflammatory cytokines IP‐10 and eotaxin‐3, antiviral gene Mx1 and viral levels were measured. Results: In the absence of IL‐13 treatment, nasal and bronchial cells showed a similar IP‐10 response in both ALI and submerged cultures. Under the ALI culture, short term (e.g., 3 days) IL‐13 treatment had a minimal effect on viral and Mx1 levels in both cell types. However, prolonged (e.g., 14 days) IL‐13 treatments in both cell types decreased viral load and Mx1 expression. Under the submerged culture, IL‐13 treatment in both cell types has minimal effects on viral load, IP‐10 and Mx1. IL‐13‐induced eotaxin‐3 production was similar in both types of cells under either submerged or ALI culture, which was not affected by viral infection. Conclusions: Our data suggest that nasal epithelial cells could serve as a surrogate to bronchial epithelial cells in future studies aimed at defining the role of type 2 cytokine IL‐13 in regulating pro‐inflammatory and antiviral responses.